Gonad Transcriptome and Whole-Genome DNA Methylation Analyses Reveal Potential Sex Determination/Differentiation Mechanisms of the Deep-Sea Mussel Gigantidas platifrons - Zhong, Zhaoshan; Wang, Minxiao; Chen, Hao; Wang, Hao; Zhang, Huan; Zhou, Li; Sun, Yan; Cao, Lei; Lian, Chao; Li, Mengna; Li, Chaolun (Frontiers in Marine Science, 2022)
Gigantidas platifrons is one of the most dominant deep-sea mussels in cold seeps ecosystems in the South China sea. Studies have shown that deep-sea mussels are a gonochoristic species, however, little is known about the molecular mechanisms of sex determination in G. platifrons. In this study, RNA-seq and WGBS methylation analysis were performed on adult G. platifrons gonads to identify potential sex-related genes and generate a comprehensive analysis of sex determination in deep-sea mussels. A total of 5923 genes were identified as differentially expressed between the ovaries and testes, of which 2711 were female-biased and 3212 were male-biased. Among them, 161 genes may participate in the sex determination, and we found that DMRT2 may play an important role in male sex determination, and FOXL2, Wnt7, and β-catenin may have impact on female sex determination. Moreover, common expression patterns were found in majority of the sex-related genes such as FOXL2, β-catenin, and genes in SOX family, suggesting the sex determination mechanisms of mussels in different habitats were conserved. The 5mC levels of transcription start sites (TSS2K) were significantly higher in sex-related genes than other DEGs in both gonads. Positive correlation was observed between sex-related genes expression and methylation in male, however, the effects of the DNA methylation on gene expression were complex in female. In short, we argue that the sex determination mechanisms of deep-sea mussel G. platifrons is mainly controlled by genetic, and the methylaion may have a regulation role of the methylation on male sex determination or differentiation.